(untitled) (Revista Diálogos, 2017)
Nas eleições ocorridas no ano de 2012, o Tribunal Superior Eleitoral veiculou na mídia de todo o país, cinco propagandas protagonizadas por atores que representavam pessoas comuns da sociedade brasileira, na tentativa de rememorar a história de mobilização da sociedade civil que resultou na criação da Lei Ficha Limpa, um dispositivo legal que entra em vigor para impedir que políticos não confiáveis, eleitos anteriormente, retornassem à vida pública, através do “voto limpo” depositado pelo eleitor na urna. Nessa linha, nos propomos compreender, através do estudo da propaganda intitulada: Campanha Eleições 2012: valorize seu voto, como se dá a construção de sentidos da expressão Vote Limpo, a partir da unidade de significação da lei e da propaganda, não como um conjunto de enunciados, mas como uma unidade de sentido que integra enunciados que se relacionam semanticamente. Para tanto, nos filiamos a Semântica do Acontecimento, elaborada por Eduardo Guimarães. In the elections held in 2012, the Electoral Superior Court spread out, in the media across the country, five advertisements, which, starring amateur actors representing ordinary and anonymous people in Brazilian society, established dialogues with readers and/or voters, recalling the story of mobilization of civil society which resulted in the creation of the Law Clean Record, a legal device that is effective for preventing unreliable politicians, elected earlier, returned to public life by "clean vote" deposited by the voter in the ballot box. Along these lines, we propose to understand, through advertising study entitled: “Election Campaign 2012: appreciate your vote”, how is the construction of meaning of the expression “Vote Clean” in advertisements from the unit of meaning of law and propaganda, not as a set of statements, but as a unit of meaning that integrates statements that relate semantically, the construction of clean Vote directions on TSE advertisement, from the texts and images as the enunciation event fragments. To conduct the analysis, we join the Semantics of Event, developed by Eduardo Guimarães.